Body-image Dissatisfaction and Weight-control Behaviour in Slovak Adolescents - Bašková, Martina; Holubčíková, Jana; Baška, Tibor (Central European journal of public health, 2017)
OBJECTIVES: The aim of the study was to examine body-image dissatisfaction in adolescents aged 13-15 years reporting to be on a diet and to assess gender and age differences in weight-reduction behaviour in Slovak adolescents. METHODS: Data on a representative sample of 2,765 adolescents (mean age 14.37 years) from the Slovak part of Health Behaviour in School Aged Children Study carried out in 2014 were analysed. Self-reported body-image dissatisfaction and engagement in weight-reduction behaviour of 13 to 15-year-old adolescents was assessed using multiple logistic regression models. RESULTS: More that 20% of boys and 35% of girls perceived themselves to be too fat. Girls reported being on a diet more frequently than boys (28.8% vs. 14.9%). The most frequent weight-reduction behaviours were drinking more water (67.7%), eating more fruits and vegetables (67.1%), and consuming fewer sweets (60.5%) and soft drinks (51.7%). Girls prevailed above boys in the use of these dietary methods. Age differences were not apparent, except for smoking, believed to help in weight reduction and used upmost by 15-year-olds (8.9%) followed by 14 and 13-year-olds, 6.0% and 4.1%, respectively. CONCLUSIONS: Body-image dissatisfaction and weight-control behaviour are issues particularly in girls, however, they did not necessarily correspond with actual obesity. The most commonly used weight-reduction behaviours are in the same way important aspects of a healthy lifestyle. There is room to improve obesity control, particularly within primary health care.
Keywords: health; Body Image; body image; chování mladistvých; mladiství; sexuální faktory; mužské pohlaví; diet; osobní uspokojení; redukční dieta; stravovací zvyklosti; Slovakia; Slovenská republika; ženské pohlaví; Humans; Sex Factors; weight-control behaviour; Personal Satisfaction; Adolescent Behavior; představa o vlastním těle; Feeding Behavior; adolescence; Female; Adolescent; Diet, Reducing; lidé; Male